ГРАВИТАЦИОННЫЕ ПРОЦЕССЫ НА КОНТИНЕНТАЛЬНОМ СКЛОНЕ КАСПИЙСКОГО МОРЯ - Маев Е.Г. (My University, 2004)
Such processes as plastic flow of unconsolidated sediments, submarine landslides, turbidity currents were studied. Factors of their rise (geologic structure, seismicity, relief and steep of the bottom, accumulation) were evaluated and the scheme of their distribution is presented. The obtained results show that neither platform tectonic regime, nor very small angle of bottom slope may secure bottom stability and absence of gravitational movements of the deposits. It should be taken into account while projecting rig bases, pipelines etc.
Keywords: 551.462.33(262.81)